The Reciprocal Paradigm of Tafsīr al-Miṣbah and Tafsīr al-Taḥrīr wa al-Tanwīr on Surah al-Baqarah verse 222 about Menstruation Blood - Halya Millati (Sawwa: Jurnal Studi Gender, 2021)
Women's misogynistic interpretation of their menstruation period as "dirt" that emerged from pre-Islamic Arab society and some classical commentators opened vast space for critics. One of the critics is the interpretation of al-Baqarah verse 222 as an effort to maintain reproduction health. This paper compares the interpretation of al-Baqarah verse 222 in Tafsīr al Miṣbaḥ by Quraish Shihab, and Tafsīr al-Taḥrīr wa al-Tanwīr, by Ibn 'Āshūr. These two interpretations are taken because they have relatively similar interpretations when interpreting al Baqarah verse 222, even though the author's historical setting is different. With the comparative method and theory of qirā’ah mubādalah, this paper answers how the interpretation of Quraish Shihab and Ibn 'Āshūr on al-Baqarah verse 222 and how the linearity of that interpretation is. This paper finds, firstly, that Quraish Shihab and Ibn 'Āshūr agree in interpreting al-Baqarah verse 222 with the prohibition of intercourse, while the wife is on her period to maintain reproduction health and interpret adhā as an uncomfortable condition. It's just that Quraish Shihab defines adhā as disturbance, while Ibn 'Āshūr means al-ḍarr (injury or danger). Secondly, the two interpretations use a reciprocal paradigm with the meaning of adhā as a disturbance or risk that can be occurred both women and men as the evidence. Thus, the reciprocal interpretation paradigm of Quraish Shihab and Ibn Asyur can become a model for an interpretation paradigm based on gender justice.